Pemanfaatan Cuka Kayu untuk Menurunkan Kadar Gas H2S (Hidrogen Sulfida) Limbah Cair Industri Tahu "X" di Tejokusuman, Notoprajan, Ngampilan, Kota Yogyakarta - Mardi Mardi; Adib Suyanto; Rizki Amalia (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Liquid waste produced from tofu industry which is containing suspended and dissolved solids will physically, chemically and biologically change. The poisonous substance yielded from the change is potential to disturb human health. The preliminary study showed that the measurement of H2S concentration in Tofu Industry “X” in its liquid waste was 0,394 mg/l or exceeding the standard threshold. One of the methods to reduce the gas is by adding wood vinegar. The study was an experiment with post test only with control group design. The amount of liquid waste sample used was 20 liter and there were three dose variations of wood vinegar observed, i.e. 5 ml, 10 ml and 15 ml for every 1000 ml liquid waste. Based on the result of One Way Anova test at 95 % level of confidence, the p-value obtained was < 0,001, which means that the various doses of wood vinegar had different effects in decreasing H2S level in tofu liquid waste. The subsequent LSD test showed that the highest mean difference with the control group was reached by Dose C (15 ml wood vinegar in 1000 ml liquid waste). However, Dose B (10 ml) was already able to fulfill the permitted threshold of 0,1 mg/l.